The energy-balanced hysteretic curve for dynamic loading. (15th February 2021) - Hernández-Montes, Enrique; Carbonell-Márquez, Juan Francisco; Gil-Martín, Luisa María
Abstract: This technical note introduces a new graphical representation which allows the visualization of the energy balance of a structure subjected to dynamic loading using hysteretic curves. Hysteretic curves were originally created to describe the behavior of magnetic materials. They were later introduced into structural engineering to describe the behavior of structures subjected mainly to seismic loading. In their current form, the hysteretic curves used in structural dynamics do not provide the information required to analyze the energy history of their behavior, this is due to the fact that velocity, a relevant variable in the description of the history of displacements, is not present. In this technical note, the authors present a new concept: the energy-balanced hysteretic curve, consisting of a graph that contains all the information needed to analyze the history of the displacements and the energy balance during the motion of the structure. Detailed examples show the benefits of this new representation.